Modeling and field-derived insights into canine leptospirosis in feral and domestic dogs of Texcoco, Mexico: A One Health approach - Salcedo-Jiménez, José; Alcala-Canto, Yazmín; Valadez-Moctezuma, Ernestina; Pérez-Rivero, Juan José (Comparative immunology, microbiology and infectious diseases, 2025)
Leptospirosis, a globally important zoonosis, poses a significant health risk to both human and animal populations. This study aimed to determine the seroprevalence of Leptospira spp. in feral and domestic dogs in Texcoco, Mexico, and to model the disease's transmission dynamics. We tested 349 asymptomatic dogs using the Microscopic Agglutination Test (MAT) for antibodies against multiple serovars. To simulate disease spread, we developed a Susceptible–Exposed–Infectious–Chronic–Recovered–Deceased (S-E-I-C-R-D) compartmental model, simulating transmission over 365 days. Overall seropositivity was 51 % (178/349), with a higher prevalence in feral dogs (55.3 %) and in non-vaccinated animals. The most frequent serovars were L. canicola (79.7 %) and L. bratislava (45.6 %). The model projected sustained transmission within the feral dog population, with prevalence peaking and stabilizing at a high level. This finding, with a simulated prevalence that approached 98 %, suggests that chronic carriers and constant environmental exposure could drive high pathogen circulation. Domestic dogs, while showing a lower simulated prevalence, likely contribute to the pathogen's persistent circulation. The combination of high field seroprevalence and model-based findings underscores that leptospirosis remains a significant public health concern in Texcoco, highlighting the urgent need for integrated control strategies that include vaccination, rodent management, and community education, aligned with a One Health approach that links animal, human, and environmental health. •Feral dogs present 8.7 times higher odds of Leptospira seropositivity than domiciled dogs.•Age is a significant risk factor, increasing the odds of Leptospira seropositivity by almost two-fold per year.•Multivariable logistic regression identifies dog status and age as key determinants of Leptospira infection risk.•High seroprevalence of Leptospira is independently associated with both feral status and increasing age in canines.